2008
DOI: 10.1016/j.biortech.2007.08.082
|View full text |Cite
|
Sign up to set email alerts
|

Effects of humic substances derived from organic waste enhancement on the growth and mineral nutrition of maize

Abstract: A physico-chemical process has been developed to transform and enhance lignocellulosic waste in liquid humic extracts: humic-like substances (HLS). The aim of this study was to determine the effects of HLS on plant physiology in order to consider their agricultural use as organic fertilizers. The effects of HLS were evaluated on maize seed germination, and their impact on growth, development and mineral nutrition was studied on maize plants cultivated under hydroponic conditions. The experimental results showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
153
0
20

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 274 publications
(194 citation statements)
references
References 31 publications
(34 reference statements)
21
153
0
20
Order By: Relevance
“…of HS to soil has been found to stimulate seed germination, and increase the growth 70 and yields of a variety of important agricultural species (Eyheraguibel et al, 2008, 71 Puglisi et al, 2009, Lee and Bartlett, 1976, Nardi et al, 2002, Arancon et al, 2006, 72 Piccolo et al, 1993. However, the effect of adding HS to plants and soils varies with 73 the origin and concentration of the HS applied, and the species of plant and soil type 74 to which it is applied (Rose et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…of HS to soil has been found to stimulate seed germination, and increase the growth 70 and yields of a variety of important agricultural species (Eyheraguibel et al, 2008, 71 Puglisi et al, 2009, Lee and Bartlett, 1976, Nardi et al, 2002, Arancon et al, 2006, 72 Piccolo et al, 1993. However, the effect of adding HS to plants and soils varies with 73 the origin and concentration of the HS applied, and the species of plant and soil type 74 to which it is applied (Rose et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…involved in cell respiration, photosynthesis, protein synthesis, water and nutrient uptake, enzyme activities (NARDI et al, 2000;TAHIR et al, 2011) and hormones (TREVISAN et al, 2010), thus stimulating plant growth. Humic substances, when applied directly onto the soil or substrate, have been used for plant production because these substances improve soil fertility and nutrient availability, according to Eyheraguibel et al (2008). Studies on the use of humic substances on fruit species are rarely reported in the literature; however, some investigations have been conducted with papaya (CAVALCANTE et al, 2011b), grape (FERRARA;BRUNETTI, 2008) and watermelon (SALMAN et al, 2005), with promising results.…”
Section: Introductionmentioning
confidence: 99%
“…Eyheraguibel et al (2008) also applied HSs via soil, in corn plants, and observed increase in shoot and root biomass. These authors attributed the benefits to the increment of up to 25% in water use efficiency by the plants that received HSs.…”
Section: Resultsmentioning
confidence: 97%